Analisis Realisasi Anggaran Belanja Dalam Mengukur Kinerja Keuangan Dengan Pendeketan Value For Money Dan Rasio Keuangan Di Kantor Kecamatan Gedeg Periode 2017-2021 - Dara Nadeya Dinanty; Nur Ainiyah; Hartono Hartono; Nurdiana Fitri Isnaini (BADAN PENERBIT STIEPARI PRESS, 2023)
The background of this research is the decrease in spending budget at the Gedeg Mojokerto District Office for the 2017-2021 period. The purpose of this study is to find out how financial performance is measured by value for money and financial ratios. This type of research uses a quantitative descriptive method using secondary data in the form of reports on the realization of the Gedeg District budget. Data collection techniques using observation techniques. The data analysis technique used is the value for money approach and financial ratios. The results of this study before the covid-19 in terms of the first method showed the criteria were quite economical, quite efficient, and very effective. Then during Covid-19 the second method gave results where the financial position at the degree of fiscal decentralization was very good, the regional government's financial dependence was very low, and less effective. Meanwhile, post-covid-19 conditions look uneconomical, quite efficient, and very effective.